Enhanced dendritic cell immunotherapy to treat glioblastoma - Adhikaree, Jason (2019)
Introduction: Glioblastoma (GBM) patients have a poor survival and are inevitably treatment refractory. The power of enhancing the immune system to combat the chemo-radiotherapy resistant tumour, melanoma, affirms the potential for re-directing the immune response against GBM. Furthermore, immunotherapy combines anti-cancer cytotoxicity with durable memory responses.